Potret Kinerja UMKM Sepatu Di Bogor Dalam Berkompetisi Pada Perekonomian Di Indonesia - Gendalasari, Gen Gen; Triandi, Triandi (Jurnal Ilmiah Manajemen Kesatuan, 2018)
The contribution of the micro, small and medium enterprises sector to gross domestic product increased from 57.84 percent to 60.34 percent in the last five years. Uptake of labor in this sector also increased, from 96.99 percent to 97.22 percent in the same period. (http://www.kemenperin.go.id, 2018), Problems with MSMEs vary, especially for shoe MSMEs. The purpose of this study, 1) What is the performance of MSME shoes in Bogor; 2) What is the model of coaching that can be developed for MSME actors The results of the study show that 1) based on evaluation it is known that the attributes of the production process, production equipment, production control, buildings and facilities, markets, quality standardization, business management, capital, and promotion require improvement. Difficulties in terms of capital make the company still survive with conventional and manual technology, so that production capacity is also relatively limited. In addition, the company's bookkeeping system is still directly controlled by the owner of the company. 2) Shoe MSMEs need guidance in terms of production processes and production facilities. As well as assistance in terms of developing market share both domestically and abroad and developing promotions so that products are more widely known